Prospective observational study on clinical and epidemiological profile of adult patients presenting to the emergency department with suspected upper gastrointestinal bleed - Alok Raj; Nidhi Kaeley; Hari Prasad; Itish Patnaik; Yogesh Bahurupi; Shrirang Joshi; Krishna Shukla; Santosh Galagali; Sanket Patel (BMC Emergency Medicine, 2023)
Abstract Background and objective Bleeding from the upper gastrointestinal (GI) tract is one of the common medical emergencies. In this study, we assessed patients’ socio-demographic and clinical characteristics and the association of clinical characteristics with treatment outcomes among patients with suspected upper gastrointestinal bleed (UGIB) presenting to the emergency department (ED). At present, there is a scarcity of data on UGIB in Northern part of India. Material and method The study was a single-center, prospective observational study conducted at an urban tertiary care center. Consecutive patients with suspected UGIB were enrolled in the study from August 2020 to February 2022. A detailed history was obtained, including demographic data such as age and sex, presenting complaints, history of presenting illness, history related to co-morbidities, addiction, and drug history. Pre-endoscopic Rockall and Glasgow-Blatchford Score were calculated for each patient. The patients were subsequently followed up till discharge from the hospital. The final outcomes with regard to mortality, need for blood transfusion, length of emergency department stay, and discharge were noted. Result 141 patients were included in the study. The mean age of the patients with suspected UGIB was 48 ± 14 years. 115 (81.6%) patients were male. The most common co-morbidity was chronic liver disease (40;28.4%). The most frequent presenting complaint in this study was hematemesis (96; 68.1%), followed by melena (76;53.9%). The mean (Standard Deviation, SD) of the Rockall Score was 2.46 ± 1.75. The mean (SD) of the Glasgow Blatchford Score was 12.46 ± 3.15 in patients with UGIB. Conclusion In our study, hematemesis was the most prevalent symptom of suspected UGIB, followed by melena. Portal hypertension was the most common cause of UGIB. Most frequent comorbidities in patients suspected of UGIB were alcohol intake, Nonsteriodal Antiinflammatory Drugs (NSAIDs) abuse, and co-morbidities such as underlying chronic liver disease, hypertension, and diabetes. Early endoscopy can be of great utility to reduce morbidity and mortality.